Nonanalytic solutions of the KdV equation - Peter Byers; A. Alexandrou Himonas (Abstract and Applied Analysis)
We construct nonanalytic solutions to the initial value problem for the KdV equation with analytic initial data in both the periodic and the nonperiodic cases.